Ethnotaxonomy As Mirrored In Sanskrit Plant Names - Patil, D A (Plantae Scientia, 2020)
The intellectual capacity of mankind for classifying natural objects and even abstract concepts is widely recognized. The rich diversity of the environment is described in sufficient details by the nomenclatural and classification systems even within ancient culture. Sanskrit is thought to be a mother of many other languages and a pristine treasure trove. Presently, it is not a language of any nation and hence remained morbid. Sanskrit literature is replete with references to plants and their utilities in ancient past. This rich Indian heritage still waits revealing its glory and secrets. The present author examined some common names of plants in Sanskrit semantically and taxonomically. The bases of coining names, roots of binomial nomenclature and scientific aspects of plant science in Sanskrit are unearthed and compared with modern phytotaxonomic systems. The merits and limits of developments are comparatively discussed highlighting elements of plant science. Studies on this line will also help earmark economic potential and ethnobotanical significance known to ancient Indians. Common plant names in Sanskrit are thus rich store-house of wisdom, knowledge, experiences and past observations of an ambient natural world.